Knowledge Management: innovation from a microenterprise perspective (Research, Society and Development, 2019)
Since the way organizations impact and impact has become more dynamic, requiring agility to adapt to market responses, organizations look to innovation to take advantage of likely opportunities. The objective is to propose indicators that allow to diagnose competencies considered ideal to the collaborators in a way that allows the qualification of the same ones and the fomentation of the skilled labor to attend the demands of the organizations in the São Paulo ABC, exactly, in the municipality of Santo André like fact of reference. In order to do so, the article will guide the qualitative research methodological approach based on a bibliographical survey and on open questions (company) to be evaluated through content analysis (Bardin) to obtain indicators that aid management in the decision-making processes regarding qualification and selection of its collaborators. As a result, one can gauge the distance between theory and practice in relation to human resources linked to the area of technology and, in conclusion, the need to develop studies in this area emerges in order to fill this gap, that is, there is still a significant gap between the individual skills and competences required to meet the organizational demands of technology companies in ABC Paulista.